Preventing Ovarian Hyperstimulation Syndrome (OHSS) - Shruti Passan (Journal of Embryology, 2025)
Ovarian Hyperstimulation Syndrome (OHSS) is a significant complication that can occur during fertility treatments, particularly in the context of assisted reproduction technologies (ART) such as In-vitro fertilization (IVF). It is characterized by enlarged ovaries and the accumulation of fluid in the abdomen and sometimes the chest, which can lead to various degrees of discomfort and, in severe cases, life-threatening complications. The incidence of clinically significant OHSS is 2-3%, however, milder forms of OHSS might develop in up to 20-30% of all IVF patients.
Keywords: Ovarian Hyperstimulation